Marketing Strategies 4 C's Affecting the Purchase Decision of Branded Bags of Students in Lat Krabang District, Bangkok - ดาวขาว, ทักษพร; คล่องแคล่ว, รัชนีภรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objective of this study was to study the 4 C’s marketing strategies that influenced the decision to buy branded bags of students in Lat Krabang District, Bangkok. This study was an approximate research using a questionnaire as a research tool. The sample group was 400 consumers in Lat Krabang District, Bangkok. The statistics used for data analysis were percentage, mean, standard deviation, and multiple regression analysis. The results of the study found that most of the sample group were females, aged 25-36 years, had a bachelor’s degree, and had an average income of 20,000-25,000 baht per month. The 4 C’s marketing mix factors in terms of consumer demand, consumer cost, consumer convenience, and communication were found to have a high mean value. It was also found that the 4 C’s marketing mix factors in terms of consumer demand, consumer cost, consumer convenience, and communication had a statistically significant effect on the decision to buy branded bags at a level of 0.05. All 4 C’s marketing mix variables could jointly affect the decision to buy branded bags of students by 74.00percent.